Effects of Money Demand on Trade Balance in Nigeria - Adeyemi, Oluwole Jacob; Oseni, Isiaq O.; Tella, Sheriffdeen A. (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
Previous studies appear to have concentrated on the effects of currency depreciation on trade balance and macroeconomic policy, while the relationship between money demand and trade balance is scantly documented in the literature. This paper therefore examines the effects of money demand on trade balance in Nigeria. For the analysis conducted, annual time series data covering the period ranging from 1986 to 2018 were used along with the Autoregressive Distributed Lag (ARDL) estimation technique. The long‑run coefficient of money demand was positively signed and statistically significant at 5% level. The positive relationship exhibited by the coefficient of money demand in the long run had a significant influence on trade balance. Thus, this implied that a unit percent increase in money demand would lead to a 1.57% significant increase in trade balance. The implication of this finding was that money demand had significantly influenced trade balance, enhancing the production of goods and fostering investment, which had led to increased growth. The paper recommends that the Central Bank of Nigeria through the Monetary Policy Committee should amend qualitative and quantitative credit control policies with the aim of improving lending to enhance the flow of credit to the real and exporting sector of the economy in order to bring about the desired effect on trade balance. However, the study is limited to an analysis of the existence of the relationship between money demand and trade balance using the Nigerian data set.